Peptide-based Fusion Inhibitors for Preventing the Six-helix Bundle Formation of Class I Fusion Proteins: HIV and Beyond - Monteiro, Ajit; Yu, Karl O. A.; Hicar, Mark D. (Current HIV Research, 2021)
A number of different viral families have developed convergent methods to infect cells. Class I fusion proteins are commonly used by members of Arenaviridae, Coronaviridae, Filovirdae, Orthomyxoviridae, Paramyxoviridae, and Retroviridae. Class I viral fusion proteins are trimers that are involved in recognizing the cellular receptor, with a region that is responsible for fusing the viral and target cell membranes. During the fusion process, the fusion region folds into a six-helix bundle (6 HB) which approximates the two membranes leading to fusion. For Human Immunodeficiency Virus (HIV), the gp41 subunit is responsible for the formation of this 6 HB. The fusion inhibitor drug enfuvirtide, or T20, is the only US Food and Drug Administration and European Medicines Agency approved drug which targets this crucial step and has been widely used in combination regimens for the treatment of HIV since March 2003. In this review, we describe the current state of peptide-based fusion inhibitors in the treatment of HIV, and review how the field of HIV research is driving advances in the development of similar therapeutics in other viral systems, including the Severe Acute Respiratory Syndrome (SARS) coronaviruses.
Keywords: T20